Loadability of Friction Stir Welded joints of High Density Polyethylene - Ebtisam Abdel-Gwad; Abu-Bakr Omar; Ahmed Radwan (Port Said Engineering Research Journal, 2015)
Development of effective welding methods for thermoplastics is still in high demand. The new friction stir welding method will be applied here on high density polyethylene (HDPE) plates to provide the designer with reliable design data relevant to room temperature practical applications because welded joints can act as a failure initiation point. This may be a result of factors such as poor welding parameters and presence of weld defects. The combination effect of travel and rotational speeds of the welding tool is investigated. Tensile, impact and fatigue tests are applied on the HDPE welded joints in order to evaluate their loadability. The tool rotational speed, travel speed and tilt angle beside tool pin length are proved determined to be important in the joint formation quality and its mechanical properties. Optimum welding parameters of 930 rpm rotation speed at 25mm/min travel speed are determined in tensile, impact and fatigue testing. An optimum value of about 90% joint efficiency is achieved in tensile test, compared to the base material. In impact and fatigue tests, brittle failure due to presence of incomplete root penetration defect, takes place like a crack starter. Maximum impact strength of about 20 KJ/m2 and fatigue life of 710 cycles are recorded and found to be too low compared to the base material. The final results indicate that friction stir welding of HDPE thermoplastics may be a valid alternative to the conventional joining techniques after elimination of the weld root defect.